2003
DOI: 10.1161/01.cir.0000093186.22847.4c
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Infarct Size and Prevention of Cardiac Rupture in Transgenic Mice Overexpressing FrzA

Abstract: Background-FrzA/sFRP-1, a secreted, frizzled-related protein and antagonist for the wnt/frizzled pathway, is expressed in the heart and vessels during mouse embryogenesis and adulthood. FrzA is involved in cell cycle control of vascular cells and angiogenesis. We assessed the hypothesis that FrzA could control the healing process after myocardial infarction (MI Early leukocyte infiltration had decreased in Tg mice during the first week. Apoptotic index was decreased by 50% in Tg mice at day 7. Matrix metallopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
220
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(224 citation statements)
references
References 30 publications
4
220
0
Order By: Relevance
“…Although the molecular mechanisms leading to cardiac rupture after MI remain poorly understood, hypertension, diabetes, cardiac hypertrophy, and use of nonsteroidal antiinflammatory agents are considered as risk factors (29,30). Mice lacking the angiotensin type 2 receptor (31), tissue-type plasminogen activator, urokinase receptor, or metalloelastase are also susceptible to cardiac rupture (32), whereas overexpression of FrzA/sFRP-1, a secreted antagonist of the Wnt/Frizzled pathway (33), and targeted deletion of matrix metalloproteinase-2 (34) and urokinase-type plasminogen activator (32) prevent cardiac rupture in mice after MI. In contrast to MuRF3, these mediators of inflammation and proteolysis are not muscle-specific and may act through different mechanisms than MuRF3 to modulate the response of the heart to acute stress.…”
Section: Discussionmentioning
confidence: 99%
“…Although the molecular mechanisms leading to cardiac rupture after MI remain poorly understood, hypertension, diabetes, cardiac hypertrophy, and use of nonsteroidal antiinflammatory agents are considered as risk factors (29,30). Mice lacking the angiotensin type 2 receptor (31), tissue-type plasminogen activator, urokinase receptor, or metalloelastase are also susceptible to cardiac rupture (32), whereas overexpression of FrzA/sFRP-1, a secreted antagonist of the Wnt/Frizzled pathway (33), and targeted deletion of matrix metalloproteinase-2 (34) and urokinase-type plasminogen activator (32) prevent cardiac rupture in mice after MI. In contrast to MuRF3, these mediators of inflammation and proteolysis are not muscle-specific and may act through different mechanisms than MuRF3 to modulate the response of the heart to acute stress.…”
Section: Discussionmentioning
confidence: 99%
“…8 Hypertension, cardiac hypertrophy, and infarct expansion are predisposing factors. Previous basic studies suggested that inhibition of plasminogen activators, MMPs, 9 or cardiac overexpression of FrzA can prevent cardiac rupture, 10 whereas deletion of angiotensin AT 2 receptor can aggravate it. 11 However, the upstream regulators of the genes that trigger these responses have not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…21) In other reports, blocking of Wnt/β-catenin signaling was shown to avert adverse remodeling or improve cardiac function in animal models of myocardial infarction. [22][23][24][25] In spite of such a context-dependency, Wnt/β-catenin signaling is thought to play a pivotal role in the progression of cardiac dysfunction/heart failure. 26) In the canonical Wnt/β-catenin pathway, DKK1 (Dickkopf1) basically inhibits the formation of a ternary complex consisting of LRP5/6, Frizzled, and the Wnt ligand followed by inhibition of the canonical Wnt/β-catenin pathway.…”
Section: Wnt/β-catenin Signaling In the Heartmentioning
confidence: 99%